2018
DOI: 10.5334/paah.4
|View full text |Cite
|
Sign up to set email alerts
|

Ba Duan Jin Preliminary Analysis of the Second Type of Plantar Pressure

Abstract: The mainly subject of this study was a common Ba Duan Jin (BDJ) practitioner. The plantar pressure distribution of nine distinct regions was analyzed during the execution of the one typical BDJ movements and Normal Walking (NK). The result of the experiment demonstrated that in BDJ movements, the pressure-time integral (PTI) of the 1st MTH was the maximum and greater than other parts in BDJ movements. The peak pressure (PP) of the 1st 2nd 3rd MTH and the GT were markedly greater than in other regions (p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Yang et al [32] inferred that the changes of autonomic balance induced by Taiji and Qigong practice may be the potential mechanism for the enhanced responses although it has not been tested. In summary, while the internal mechanisms remain inconclusive, it is well-established that there are several links between neuroendocrine factors and exercise that could impact positively on the cells of the immune system [47][48][49][50][51][52][53]. More physiological studies are much warranted to further reveal the associated mechanistic biochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [32] inferred that the changes of autonomic balance induced by Taiji and Qigong practice may be the potential mechanism for the enhanced responses although it has not been tested. In summary, while the internal mechanisms remain inconclusive, it is well-established that there are several links between neuroendocrine factors and exercise that could impact positively on the cells of the immune system [47][48][49][50][51][52][53]. More physiological studies are much warranted to further reveal the associated mechanistic biochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Gait analysis has been used to identify intrinsic gait-related risk factors, which revealed altered ankle joint sagittal plane kinematics and plantarflexion moments compared to the uninjured side [35]. Increased ankle dorsiflexion was accompanied by decreased plantarflexion and was observed almost during the whole stance phase of walking, jogging and running movements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the reduced work of skeletal muscle is associated with muscle fatigue, which was believed to be a potential cause of increased injury rates for athletes during unexpected perturbations (Hassanlouei et al, 2012). Additionally, in racket sport players, there is a potential source of muscle asymmetry between two legs, which could largely affect the pattern of movement and perhaps induce sport injuries (Ye, Sun & Fekete, 2018; Lam et al, 2018; Ireland et al, 2013; Sanchis-Moysi et al, 2010). The less adept lower limb for balance, the greater the inability to provide an optimally stable base for the neuromuscular system to maintain a constant tension.…”
Section: Discussionmentioning
confidence: 99%